2015
DOI: 10.1002/ijop.12207
|View full text |Cite
|
Sign up to set email alerts
|

Chinese undergraduates' preferences for altruistic traits in mate selection and personal advertisement: Evidence from Q‐sort technique

Abstract: Human's preferences for altruistic mates have been confirmed by many researchers. Under the deep influence of Confucianism that authorised more parental control over offspring's mate selection, Chinese people's mating strategies and mate preferences may be different from what the evolutionary psychologists have suggested. This study used the Q-sort technique to assess the roles of altruistic traits in mate selection and personal advertisement. A total of 200 university students participated in the Q-sort proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 30 publications
0
16
1
1
Order By: Relevance
“…This therefore suggests that prosociality acts predominantly as a signal of an individual's quality as a partner and/or parent. However, other findings suggest no difference in the effects of prosocial behaviour for short-or long-term mating opportunities (Arnocky et al, 2016;Guo et al, 2015). These latter findings suggest further investigation of the temporal mating context when researching prosociality is warranted.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…This therefore suggests that prosociality acts predominantly as a signal of an individual's quality as a partner and/or parent. However, other findings suggest no difference in the effects of prosocial behaviour for short-or long-term mating opportunities (Arnocky et al, 2016;Guo et al, 2015). These latter findings suggest further investigation of the temporal mating context when researching prosociality is warranted.…”
mentioning
confidence: 94%
“…For instance, studies have found that individuals increase their prosocial behaviour in mating scenarios, such as when being observed by potential mates (Bhogal, Galbraith, & Manktelow, 2016b;Farrelly, Lazarus, & Roberts, 2007;Iredale, Vugt, & Dunbar, 2008;Tognetti, Berticat, Raymond, & Faurie, 2012;Tognetti, Dubois, Faurie, & Willinger, 2016) and also when competing with others (Raihani & Smith, 2015;Tognetti et al, 2016). Furthermore, it has also been shown that prosocial individuals are consistently considered more desirable than their non-prosocial counterparts (Barclay, 2010;Farrelly, 2011Farrelly, , 2013Guo, Feng, & Wang, 2015;Moore et al, 2013;Oda, Okuda, Takeda, & Hiraishi, 2014;Oda, Shibata, Kiyonari, Takeda, & Matsumoto-Oda, 2013;Phillips, Barnard, Ferguson, & Reader, 2008). Furthermore, it has also been shown that prosocial individuals are consistently considered more desirable than their non-prosocial counterparts (Barclay, 2010;Farrelly, 2011Farrelly, , 2013Guo, Feng, & Wang, 2015;Moore et al, 2013;Oda, Okuda, Takeda, & Hiraishi, 2014;Oda, Shibata, Kiyonari, Takeda, & Matsumoto-Oda, 2013;Phillips, Barnard, Ferguson, & Reader, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A particularly important context to consider is the role of length of relationship. Here there is very strong experimental support for prosocial behaviors being more desirable for longer relationships (Barclay 2010;Farrelly 2011;Farrelly et al 2016;Guo et al 2015;Moore et al 2013;Oda et al 2014), as well as having an important role cross-culturally in actual long-term relationships (Stavrova & Ehlebracht 2015;Tognetti et al 2014). This suggests that prosocial behavior is signaling good phenotypic quality, that is, the ability of the signaler to provide and support as a good partner or parent (Farrelly 2011;Kokko 1998;Miller 2007).…”
Section: Daniel Farrellymentioning
confidence: 94%
“…Little research exists to answer this, but a recent study found that behaving fairly occurred more than overall prosociality toward physically attractive partners in an ultimatum game (Bhogal et al 2016). Elsewhere, Guo et al (2015) found that a cultural norm among Chinese undergraduates had a great influence over the role of kin altruism, making this type of prosocial behavior unusual in mate choice as it was preferred more by men (and signaled more by women). Finally, heroism can be considered an additional category of prosocial behavior, which, although it too has been shown to be an important trait in mate choice (Farthing 2005;Kelly & Dunbar 2001) and therefore more likely to be biased toward attractive individuals, is unfortunately not addressed in the target article.…”
Section: Daniel Farrellymentioning
confidence: 99%